Using Grapevine Water Status Measurements for Irrigation Scheduling of Table Grapes - A Review - Howell, C.L.; Myburgh, P.A. (South African Journal of Enology and Viticulture, 2023)
Water is becoming an increasingly scarce resource, so agriculture competes with urban and industrial needs for water. The production of table grapes with high export potential is the objective of South African producers. Growth, production, ripening aspects and quality parameters of table grapes can potentially be manipulated by means of irrigation. Consequently, it is an important management practice to help ensure economically viable table grape production. The objective for optimum irrigation scheduling should be to combine soil and plant water status measurements to calibrate grapevine water potential against reliable soil water monitoring instruments. Considering previously reported literature, poorer vegetative growth was related to lower levels of leaf water potential (YL). Given that berry size is a crucial aspect for yield as well as quality, it was evident that low levels of water potential can restrict berry development, thereby reducing berry size. Bunch mass was lower where there were lower levels of YL, pre-dawn leaf water potential (YPD) and total diurnal water potential (YTot). Poorer yield was generally related to lower levels of YL experienced throughout the season. However, lower levels of YL in the post-veraison period did not affect grapevine yield. The juice TSS did not respond to levels of YL but juice total titratable acidity (TTA) was related to lower levels of YL. Grape colour was affected where wet soil conditions induced higher levels of YL as well as where dry soil conditions induced lower levels of YL.